2015
DOI: 10.4102/ajlm.v4i1.137
|View full text |Cite
|
Sign up to set email alerts
|

Virulence and pathogenicity of three <i>Trypanosoma brucei rhodesiense</i> stabilates in a Swiss white mouse model

Abstract: Background: A key objective in basic research on human African trypanosomiasis (HAT) is developing a cheap and reliable experimental model of the disease for use in pathogenesis and drug studies.Objective: With a view to improving current models, a study was undertaken to characterise the virulence and pathogenicity of three Trypanosoma brucei rhodesiense stabilates, labelled as International Livestock Research Institute (ILRI)-2918, ILRI-3953, and Institute of Primate Research (IPR)-001, infected into Swiss w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…The present study recorded tissue inflammation in mice infected with the two forms and was in consistent with previous observations [27,51]. Trypanosome-induced inflammation lesions were more intense in CNS than in BSF derived trypanosomes infected mice which could be informed by the enhanced tissue invasion in CNS infected mice.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The present study recorded tissue inflammation in mice infected with the two forms and was in consistent with previous observations [27,51]. Trypanosome-induced inflammation lesions were more intense in CNS than in BSF derived trypanosomes infected mice which could be informed by the enhanced tissue invasion in CNS infected mice.…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, our results showed that at the end of experiment the spleen and liver organs of BSF and CNS infected mice were heavier when compared with the non-infected control. Our findings showed short survival times for mice infected with EATRO 2291 and KETRI 2656 demonstrating the two isolates as the most virulent among isolates used in this study [27,38].…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…brucei) , the donor mice were anaesthetized using carbon dioxide, the parasites collected through cardiac puncture in tubes containing 10% EDTA and quantified using improved Neubauer chamber method of [23] The parasites (in blood) were subsequently diluted to 1.0 x 10 4 trypanosomes/mL with Phosphate-buffered-Saline-Glucose (PSG) (44 mM NaCl, 57 mM Na 2 HPO 4 , 3 mM KH 2 PO 4 , 55 mM glucose) pH 8.0 solution. Subsequently, five groups of six mice [5,24,25]each were intraperitoneally, subcutaneously, intramuscularly, intradermaly or intravenously inoculated with 0.1mL (1.0 x 10 4 trypanosomes) of the T . brucei or T .…”
Section: Methodsmentioning
confidence: 99%
“…Gating strategies are given in S4 and S5 Figs. of motor dysfunction are often present in HAT and were reported in mice infected with T. b. gambiense or with T. b. rhodesiense [41,42]. Although we have not directly analyzed parasite penetration in the brain nor the extension of neuroinflammation, the appearance of the motor disorders in the infected mice can be considered an indirect sign of neurodegeneration, and therefore, helped to assess the contribution of TbISP2 to pathogenicity.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 97%